Different effects of swamp probiotics application frequency as a biofloc-forming agent on the production of catfish (Clarias gariepinus) - Mohamad Amin; Retno Cahya Mukti; Ferdinand Hukama Taqwa; Andini Andini; Marsi Marsi; Langgeng Priyanto; Marini Wijayanti (Depik, 2024)
Catfish (Clarias gariepinus) that are reared with probiotics as biofloc-forming agent is thought to increase the fish production. Applying swamp probiotics to the water media has never been studied to ensure the flocks' availability in the rearing media. This study aimed to determine the appropriate frequency of probiotics application collected from swamps for biofloc formation to improve the catfish production. This study used a completely randomized design with two treatments and three replications. The treatments were composed of different application frequency of swamp probiotics: (P1) once in 42 days of rearing and (P2) twice in 42 days of rearing. Data on flock volume, total bacterial colonies, absolute growth rate, feed efficiency, survival rate, and water quality were analyzed by T-test with a 95% confidence level. Meanwhile, the flock composition data were analyzed descriptively. The results showed that P2 obtained the best treatment with a floc volume of 68.33 10.41 mL/L, absolute length growth of 8.18 1.03 cm, absolute weight growth of 19.30 3.12 g, feed efficiency of 135.24 7.98%, survival rate of 89.33 6.21%, biomass production of 24639.50 1344.51 g, temperature of 28.85-29.59C, pH of 7.27-7.42, dissolved oxygen (DO) of 3.91-5.72 mg/L, ammonia of 0.45-1.15 mg/L, and total dissolved solids (TDS) of 717.33-885.50 mg/L. Therefore, swamp probiotics should be applied to catfish culture media twice for 42 days of rearing or once every 21 days.Keywords:BioflocCatfishProbiotics from swamp